Determination of cadmium, lead, copper and arsenic in raw cocoa, semifinished and finished chocolate products - Lee, C. K.; Low, K. S. (Universiti Pertanian Malaysia, 1985)
The levels of cadmium, lead, copper and arsenic were determined in two batches of raw cocoa and semifinished chocolate products sampled at various intermediate stages of the manufacturing process. The metal contents of eighteen chocolate bars produced by four chocolate making factories were also determined. A nalyses of the metal contents in cocoa containing samples were effected by dry ashing of the samples at 450°C, followed by inductively coupled plasma atomic emission spectrometry. Average recoveries of 90 to 97% were obtained for the metals when the samples were spiked with known concentrations of metals. The variations in the metal contents of raw cocoa, semifinished and finished products show that there were no effective contaminations of metals during the manufacturing process; the amount of metals in the finished products corresponded to the fraction of cocoa mass present. The metal contents of locally produced chocolates were within acceptable levels except for arsenic which bordered on the limit.